2021
DOI: 10.3389/fsurg.2021.673847
|View full text |Cite
|
Sign up to set email alerts
|

Endolymphatic Hydrops in Fluctuating Hearing Loss and Recurrent Vertigo

Abstract: Background: Endolymphatic hydrops (EH) is the histopathological hallmark of Ménière's disease (MD) and has been found by in vivo magnetic resonance imaging (MRI) in patients with several inner ear syndromes without definite MD criteria. The incidence and relevance of this finding is under debate.Purpose: The purpose of the study is to evaluate the prevalence and characteristics of EH and audiovestibular test results in groups of patients with fluctuating audiovestibular symptoms not fulfilling the actual crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…There are histopathological and electrophysiological reports suggesting endolymphatic hydrops in the contralateral ear (34)(35)(36). Finally, Pyykkö et al reported the presence of endolymphatic hydrops in 65% of contralateral ears of subjects with clinically unilateral MD as assessed with gadolinium-enhanced MRI (37), and we also in cases with fluctuating auditory or vestibular symptoms (38). Contrary to these hypotheses (the push-pull mechanism between co-planar canals through the commissural system or subclinical disease) is our finding that the modification in the gain of the VOR in those ears is not significantly different to the spontaneous modifications as shown when comparing to results in group 0.…”
Section: Discussionsupporting
confidence: 57%
“…There are histopathological and electrophysiological reports suggesting endolymphatic hydrops in the contralateral ear (34)(35)(36). Finally, Pyykkö et al reported the presence of endolymphatic hydrops in 65% of contralateral ears of subjects with clinically unilateral MD as assessed with gadolinium-enhanced MRI (37), and we also in cases with fluctuating auditory or vestibular symptoms (38). Contrary to these hypotheses (the push-pull mechanism between co-planar canals through the commissural system or subclinical disease) is our finding that the modification in the gain of the VOR in those ears is not significantly different to the spontaneous modifications as shown when comparing to results in group 0.…”
Section: Discussionsupporting
confidence: 57%
“…However, it is also very important to know in depth the elimination pathways of the substance, not only to prevent possible dysregulation of the labyrinth fluids with the subsequent iatrogenic endolymphatic hydrops but also to assess a possible toxicity effect at the cochlear and vestibular levels ( 40 ). Moreover, it is widely recognized that there is not always a direct correlation between endolymphatic hydrops and the symptomatology experienced by the patient ( 41 , 42 ). To this extent, the histological findings evidenced in this study show only some kinds of hydrops, not necessarily related to functional outcomes, and additional research ought to be done to objectively evaluate the proper performance of the vestibular end organs following inner ear drug delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study by Pérez-Fernández et al [ 29 ] examined the severity of endolymphatic hydrops in the cochlea and vestibule of patients with unilateral definite MD ( n = 22) with respect to the results from the caloric test and vHIT; they found that there was a significantly higher degree of hydrops in the ear of patients with abnormal caloric test findings but normal vHIT results. They were led to conclude that endolymphatic hydrops severity in magnetic resonance imaging (MRI) evidences disparate vestibular test results [ 29 , 30 ]. Additionally, in gadolinium-contrasted MRI, previous studies confirmed that patients with MD showed endolymphatic hydrops (EH) in the vestibulum more frequently than in the cochlea, whereas EH was rare in patients with VM.…”
Section: Discussionmentioning
confidence: 99%